Media Sosial Adalah Ilusi: Kecenderungan Palsu di Media Sosial – Tinjauan Sistematis - Iqlima Pratiwi; Suryanto Suryanto; Wiwin Hendriani (Society, 2025)
The expansion of social media platforms has made it easier for people to present themselves online. However, this self-presentation is often carried out by displaying only the most favorable aspects of oneself, with little consideration for authenticity. Such behavior becomes a form of faking tendency aimed at gaining advantage through curated self-presentation. This tendency may alter and influence an individual’s self-concept as they attempt to stay aligned and consistent with the image they present on social media. Yet these alterations cannot change the fact that their online persona may remain far removed from their actual identity. A total of 10 articles were included in this review. The methodology began with a selection of studies based on their basic characteristics and relevance to the topic. Second, all selected articles were summarized and reviewed. Third, the information gathered from the review was synthesized, including the effects of self-presentation on self-concept, the processes of self-concept alteration, and the faking tendencies that may emerge during these processes. Overall, this article outlines several potential directions for future research.